Pengaruh pendanaan investasi pada proyek konstruksi - Indrawan, Aprianto Donny; Muhamaddan, Abdullah Khoir (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The state budget has limitations to meet all infrastructure needs from Sabang to Merauke. As an illustration, based on previous projections by measuring the ability of the 2020-2024 APBN, the government is estimated to be only able to meet 30 percent or around Rp. 623 trillion of the total budget requirement for infrastructure provision of Rp. 2,058 trillion. The remaining 70 percent or IDR 1,435 trillion is then a gap that must be funded from outside the budget, in this case funding from government cooperation with business entities (private investors), BUMN / BUMD, or funding from loans (loans) and foreign grants. The assessment is carried out with the problem approach used, namely an inventory of existing infrastructure project plan data with ongoing project data using investment and loan funding with a qualitative analysis method by producing a description of the data in the form of sentences that are arranged regularly. The results of this study indicate that the source of investment funding and foreign loans (loans) have a large effect and become an alternative to the acceleration of infrastructure development in Indonesia so that the Medium or Long Term Development Plan can be achieved.